In Silico Discovery and Optimisation of a Novel Structural Class of Hsp90 C-Terminal Domain Inhibitors - Živa Zajec; Jaka Dernovšek; Martina Gobec; Tihomir Tomašič (Biomolecules, 2022)
Hsp90 is a promising target for the development of novel agents for cancer treatment. The N-terminal Hsp90 inhibitors have several therapeutic limitations, the most important of which is the induction of heat shock response, which can be circumvented by targeting the allosteric binding site on the C-terminal domain (CTD) of Hsp90. In the absence of an Hsp90—CTD inhibitor co-crystal structure, the use of structure-based design approaches for the Hsp90 CTD is difficult and the structural diversity of Hsp90 CTD inhibitors is limited. In this study, we describe the discovery of a novel structural class of Hsp90 CTD inhibitors. A structure-based virtual screening was performed by docking a library of diverse compounds to the Hsp90β CTD binding site. Three selected virtual hits were tested in the MCF-7 breast cancer cell line, with compound TVS-23 showing antiproliferative activity with an IC50 value of 26.4 ± 1.1 µM. We report here the optimisation, synthesis and biological evaluation of TVS-23 analogues. Several analogues showed significantly enhanced antiproliferative activities in MCF-7 breast cancer and SK-N-MC Ewing sarcoma cell lines, with 7l being the most potent (IC50 = 1.4 ± 0.4 µM MCF-7; IC50 = 2.8 ± 0.4 µM SK-N-MC). The results of this study highlight the use of virtual screening to expand the structural diversity of Hsp90 CTD inhibitors and provide new starting points for further development.